(untitled) - Black, Christopher (New York, 2017)
4 full-length practice SATs in the book, including a Diagnostic test. Comprehensive overview of the current test format, including information on scoring. Realistic practice questions with thorough answer explanations that reflect Evidence-Based Reading and Writing, heart of Algebra, and all other questions types you'll see on test day Specific tips for mastering the Reading Comprehension section you won't find anywhere else. Hundreds of Math practice questions like the ones on the SAT, covering both grid-ins and multiple choice answers. Extensive challenge problems throughout the book that reflect the SAT's most difficult concepts. A FREE customizable test planner app to help you organize your study schedule.
Keywords: SAT (Educational test),SAT (Kiểm tra giáo dục); Study guides,Hướng dẫn học